Metapoetry and self-referentiality in Paulo Leminski’s antilyric - Sérgio Roberto Massagli (Texto Poético, 2019)
In metapoetictexts poetry becomes matter of itself. Thus, in exercising metapoetry, the poet reveals his critical awareness of the intricate relationship language holds with the world. The poetic and critical production of Paulo Leminski, written between the 1960s and1980s, presentes an uneasiness and brings to the debate the problematic relationship in the contemporaneity between thought, world and language. The purpose of this work is to seek the traces of this selfreflexive writing in the confrontation between his prose essays and his poetic production.